THE INFLUENCE OF PERSONALITY AND SPIRITUAL COMPETENCIES ON EMPLOYEE PERFORMANCE AT THE PEOPLE'S WELFARE BUREAU OF THE GOVERNOR'S OFFICE OF NORTH SUMATRA - Ray, Maya Divia (Proceeding International Seminar of Islamic Studies, 2024)
The goal to be achieved in conducting this research is to determine the effect of personality and spiritual competence on employee performance at the People's Welfare Bureau, Office of the Governor of North Sumatra, partially and simultaneously. This research was aimed at all employees of the People's Welfare Bureau of the North Sumatra Governor's Office, totaling 40 employees. The research method used by the author is a quantitative method. Data collection techniques using questionnaires, documentation studies, observations and interviews. The results of the study partially show that the Personality Competency variable (X1) has a positive and significant effect on Employee Performance (Y) at the People's Welfare Bureau, North Sumatra Governor's Office. And the Spiritual variable (X2) has a positive but not significant effect on Employee Performance (Y). Simultaneously Personality and Spiritual Competence have a positive effect on Employee Performance at the People's Welfare Bureau, North Sumatra Governor's Office.